PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE GROUP INVESTIGATION (GI) UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS III SD NEGERI 009 KAMPUNG DALAM PARIT I/II KECAMATAN SUNGAI APIT - ', Ernawati; Kurniaman, Otang; Witri, Gustimal (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: Application of Cooperative Learning Model Group Investigation (GI) in the Learning science aimed at translating the abstract more concrete material, so the material can be conveyed and students absarak Sakan understand and enable the understanding will be stored in the memory of students. This research aims to design programs of learning programs with the application of cooperative learning model of Group Investigation (GI) so that it can improve student learning outcomes, especially the subject of the motion of objects. the implementation of cooperative learning model of Group Investigation to improve learning outcomes IPA third grade students of SDN. 009 Kampung Dalam Kacamatan Sungai Apit. This data was obtained from the data class act. With the formulation of the problem "Is learning model application koopertif group investigation IPA can improve learning outcomes of students on the subject of the motion of objects of class III SDN. 009 Kampung Dalam Kacamatan Sungai Apit ''. explained that the first meeting of the first cycle of the score obtained from the activity of the teacher is the first meeting of the percentage gain of 66.6% and a meeting kedua75% with good category. Meanwhile, the first meeting of the second cycle of activity the teachers gained 91.66% and 95.8% the second meeting. Activities of students from the first cycle to the second cycle increased from 64% to 81.2% in the category both in the second cycle. An increase of 17.2%. Data in the form of class action replay test students' understanding on the first cycle at 64% and 81.2% silkus II besides an increase of 52.17%. Keywords: Cooperative Learning Model Group Investigation, learning outcomes IPA